PENGARUH MANAJEMEN LABA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013-2016) - Nur Gandhi Mahesti; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2019)
The research aims to analyze the influence of earnings management on Corporate Social Responsibility disclosures used control variables include size, leverage and return on assets (ROA). This research used 280 samples of manufacturing firms listed in Indonesian Stock Exchage (IDX) during 2013 to 2016. The sampling method is purposive one. Data analyzed used multiple regression.The results show that earnings management positivly to Corporate Social Responsibility disclosures. This study showed companies that do earnings management tend to make high Corporate Social Responsibility disclosures than companies that does not earnings management.